Social inequalities in self-perceived health in Chile, does the urban environment matter?: a cross-sectional study - Natalia López-Contreras; Vanessa Puig-Barrachina; Alejandra Vives; Paola Olave-Müller; Mercè Gotsens (BMC, 2023)
Abstract Background The health of a population is determined by urban factors such as the physical, social and safety environment, which can be modified by urban regeneration policies. The aim of this study was to analyze the associations of elements of the social, physical and safety environment of the neighborhood in the urban context with self-perceived health (SPH), according to axes of inequality, such as gender and educational level in Chile in 2016. Methods Cross-sectional study using a nationally representative population-based survey of Chile. We used data from the 2016 National Survey of Quality of Life and Health. Poor SPH in the urban population older than 25 years was analyzed in relation to social, physical and safety environment variables. Poisson multilevel regression models were estimated to obtain prevalence ratios (PR) and their respective 95% confidence intervals (95%CI). All analyses were stratified by sex and educational level. Results SPH was worse in women than in men, especially in those with a lower education level. Poor SPH was associated with lack of support networks (PR = 1.4; 95%CI = 1.1-1.7), non-participation in social organizations (PR = 1.3; 95%CI = 1.1-1.6) and perceived problems with the quality of public space (PR = 1.3; 95%CI = 1.2-1.5) in women with a medium-high educational level and with a feeling of not belonging to the neighborhood (PR = 1.5; 95%CI = 1.2-1.8) and the perception of pollution problems (PR = 1.2; 95%CI = 1.0-1.4) in women with a low educational level. A feeling of unsafety was associated with both educational levels (PR = 1.3; 95%CI = 1.0-1.5). Poor SPH was associated with the feeling of not belonging (PR = 1.7; 95%CI = 1.2-2.5), and unsafety (PR = 2.1; 95%CI = 1.8-2.4) in men with a medium-high educational level, while there were fewer associations in men with a lower education level. Conclusions Urban interventions are recommended to improve the health of the resident population and should take into account axes of inequality.